Coping and Adaptation Strategies by Small-Scale Farmers in the Pru district of Ghana: Legal Orders Imposed by State and Non-State Actors - Quansah, Charles; Mensah, Ronald Osei; Yeboah, Isaac (Technium Social Sciences Journal, 2022)
The Pru district has been affected by large-scale land acquisition activities as most smallholder farmers have been affected. However, this study teased out the coping and the adaptation strategies of smallholder farmers to mitigate the effects of large-scale land acquisition in the Pru district in the Bono East Region of Ghana. The study employed a mixed methods (quantitative and qualitative) approach, where farming households and smallholder farmers were interviewed. Focus group discussions were also conducted to solicit data from farmer-based associations to help in the attainment of the objectives of the study. Primary and secondary sources of data were employed in the study. The qualitative data was analyzed thematically. The study found out that smallholder farmers cope and adapt to a situation differently as most cope with the re-location of farms too far places by leaving the house early and reducing the number of days of visit as smallholder farmers bought motorbikes as their adaptive strategies. The study revealed that smallholder farmers engaged in fishing activities, keeping backyard gardening and depending on family and friends for support as a coping and adaptation strategy.